A bioinspired metal–organic approach to cross-linked functional 3D nanofibrous hydro- and aero-gels with effective mixture separation of nucleobases by molecular recognition. Issue 27 (3rd July 2020) - Vegas, V. G.; Beobide, G.; Castillo, O.; Reyes, E.; Gómez-García, C. J.; Zamora, F.; Amo-Ochoa, P.
Abstract : The direct reaction between Cu(CH3 COO)2 and uracil-1-acetic acid in water gives rise to the formation of a hydrogel consisting of entangled nanometric ribbons of a 1D Cu(ii ) coordination polymer (CP) decorated with biocompatible uracil nucleobases. Abstract : The direct reaction between Cu(CH3 COO)2 and uracil-1-acetic acid in water gives rise to the formation of a hydrogel consisting of entangled nanometric ribbons of a crystalline antiferromagnetic 1D Cu(ii ) coordination polymer (CP) decorated with biocompatible uracil nucleobases. This hydrogel is the precursor for the preparation of a meso/macroporous ultralight aerogel that shows a remarkable Young's modulus. As a proof-of-concept of the molecular recognition capability of the terminal uracil moieties anchored at Cu(ii ) CP chains, this material has been tested as the selective stationary phase for the separation of nucleobase derivatives in HPLC columns.